Transformational and transactional leadership, organizational support and environmental competition intensity as antecedents of intrapreneurial behaviors - Galit Klein (European Research on Management and Business Economics (ERMBE), 2023)
In an era of constant changes, organizations need to promote innovative thinking that leads to intrapreneurial behaviors. The current study aims to explore how leadership style (transformational and transactional leadership), organizational support for entrepreneurship, and the intensity of competition relate to employee intrapreneurial behaviors. Two studies were conducted to answer the research questions. In the first study, a paper-based survey was distributed to 464 employees. Following the first study's result, 150 manager-employee dyads were examined. Employees were asked to evaluate their manager's leadership style and the amount of organizational support, while their managers evaluated the employee's intrapreneurial behaviors and the intensity of the competition in the organization's environment. The results show that both transformational leadership and transactional leadership are connected to intrapreneurial behaviors via the mediation of organizational support. However, in a highly intense competitive environment, transformational leadership exhibits a stronger relationship with organizational support, which mediates the connection of the former with intrapreneurial behaviors. The results of the current study extend previous findings suggesting that both transformational and transactional leadership have positive effects on employee intrapreneurial behaviors. However, to actualize intrapreneurial development, an organization must provide support and help allocate both tangible and intangible resources accordingly.
Keywords: M12; O31; O32; 650; Transformational and transactional leadership; Intrapreneurial behaviors; Organizational support for entrepreneurship